Is Lugol necessary for endoscopic resection of esophageal squamous cell neoplasia? - Costa-Santos, Maria Pia; Ferreira, Alexandre Oliveira; Mouradides, Christina; Pérez-Cuadrado-Robles, Enrique; Yeung, Ralph; Garcés-Duran, Rodrigo; Snauwaert, Christophe; Dano, Hélène; Piessevaux, Hubert; Deprez, Pierre H. (Endoscopy International Open, 2020)
Background and study aims Recent evidence suggests that lugol chromoendoscopy (LCE) and narrow-band imaging (NBI) have comparable sensitivity for detection of superficial esophageal squamous cell carcinoma (SCC). However, LCE is time-consuming and associated with side effects. The aim of this study was to compare the effectiveness of NBI and LCE in defining resection margins of esophageal SCC.Patients and methods This was a retrospective observational cohort study of patients with esophageal SCC and dysplasia who underwent en-bloc resection between 1999 and 2017 at the Cliniques universitaires Saint-Luc, Brussels. Two groups were defined: 1) inspection with NBI only; and 2) inspection with LCE (with or without NBI). The primary endpoint was complete lateral resection rate. Multivariate regression was used to adjust for potential confounders.Results A total of 102 patients with 132 lesions were included. Lesions were inspected with LCE in 52 % (n = 68) and with NBI only in 48 % (n = 64). Lesions 0-IIa were more frequent in the NBI group (37 %) and 0-IIb (60 %) in LCE. Lesion location, size, and histology and resection technique (endoscopic submucosal dissection in 122/132 cases, 92 %) were similar between the groups. The rate of complete lateral resection for invasive carcinoma was 90 % in LCE group and 94 % in NBI group (P = 0.498) and 65 % and 67 % (P = 0.813), respectively, for dysplasia complete lateral resection. These results remained non-significant after adjusting for potential confounders. Conclusions Mucosal inspection and delineation of tumors with lugol chromoendoscopy before endoscopic resection of esophageal squamous cell lesions was not associated with increased complete lateral resection rate when compared to NBI.